HYPERTENSION AWARENESS FOR A HEALTHIER FUTURE: COMMUNITY SCREENING AND EDUCATION IN TIRTAJAYA, DEPOK CITY - Rizky Farmasita Budiastuti (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
Hypertension is a global health concern that can lead to serious complications such as stroke and heart failure. According to the WHO, 1.28 billion adults worldwide suffer from hypertension, with two-thirds living in low- and middle-income countries. Many remain unaware of their condition due to its asymptomatic nature. This study aimed to conduct blood pressure screening and assess risk factors for hypertension to increase community awareness of early detection. The community service activity was held in Tirtajaya Urban Village, Sukmajaya Subdistrict, Depok City, involving 54 participants. Data were collected through blood pressure measurements and structured questionnaires covering lifestyle, diet, and knowledge about hypertension. The program also included health education provided by pharmacists and pharmacy students, focusing on lifestyle-based prevention and management of hypertension. Results showed that more than 50% of participants had elevated blood pressure: 39% were categorized as pre-hypertensive, 28% with stage 1 hypertension, and 15% with stage 2 hypertension. About 57% of participants were physically inactive, 65% had unhealthy eating habits, and 26% were smokers. Knowledge of causes and prevention of hypertension was relatively good, though understanding of early symptoms was still limited. These findings underscore the importance of routine screening and the pharmacist’s role in community health education to help reduce hypertension prevalence.